Scrutinizing Raw Material between China and Italy: the Various Processing Sequences of Bombyx mori Silk - Sophie Desrosiers (L'Atelier du CRH)
Silk yarn may be transformed according to three distinct processing sequences, each producing silk cloths with specific aesthetic qualities. But only silks considered as ‘luxury’ ones, woven through one process, have attracted in-depth research. Through unveiling the characteristics of the three chaînes opératoires of silk processing, and of the silks that they produce, this article aims at revealing their diversity and at providing tools to distinguish them in written, visual, and material sources. The examination of various sources tends to demonstrate the economic, social and cultural importance of the three types of silks produced in China during the Han and Tang dynasties, then in Italy when silk weaving began in the late Middle Ages. Through a specific attention to yarn twisting, it appears that during the 15th century some Florentine silk workers were acting with implements and a body language similar to those active in China since at least the beginning of the Christian Era. It shows once more that the Orient had a great influence not only on Italian silk designs and weaves, but also on the simplest implements and gestures of their makers